2007
DOI: 10.1007/s10530-007-9097-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of invasive Spartina growth stages on associated macrofaunal communities

Abstract: In coastal wetlands, invasive plants often act as ecosystem engineers altering flow, light and sediments which, in turn, can affect benthic animal communities. However, the degree of influence of the engineer will vary significantly as it grows, matures and senesces, and surprisingly little is known about how the influence of an ecosystem engineer varies with ontogeny. We address this issue on the tidal flats of San Francisco Bay where hybrid Spartina (foliosa · alterniflora) invaded 30 years ago. The invasion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 33 publications
3
38
0
Order By: Relevance
“…The only two annelid species that were abundantly present in the Spartina vegetation were the polychaete Heteromastus filiformis and oligochaetes. Both are small, sub-surface deposit feeding species, often reported in other studies to be common in Spartina vegetations (e.g., Neira et al 2005Neira et al , 2007. Particularly oligochaetes can reach high abundances in salt marshes, as they can live in the microhabitat created by the root system of the plants and are capable to feed upon Spartina detritus .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The only two annelid species that were abundantly present in the Spartina vegetation were the polychaete Heteromastus filiformis and oligochaetes. Both are small, sub-surface deposit feeding species, often reported in other studies to be common in Spartina vegetations (e.g., Neira et al 2005Neira et al , 2007. Particularly oligochaetes can reach high abundances in salt marshes, as they can live in the microhabitat created by the root system of the plants and are capable to feed upon Spartina detritus .…”
Section: Discussionmentioning
confidence: 91%
“…This allowed a significantly higher endofaunal species richness, abundance and biomass in the Spartina patch as compared to the Spartina marsh. Along a sequence of stages in the invasion of a hybrid Spartina, from tidal flat to dieback, Neira et al (2007) observed cascading changes in sediment conditions that led to a substantial reduction in macrobenthic species richness, increased dominance and a shift in feeding modes.…”
Section: Discussionmentioning
confidence: 99%
“…An adequate understanding of these two components of S. alterniflora spread will necessarily feature a blend of biological and stochastic mechanisms (Taylor et al 2004). S. alterniflora is a powerful ecosystem engineer (Neira et al 2007) that severely disrupts the trophic structure of intertidal estuarine lands (Levin et al 2006). The removal of S. alterniflora from Willapa Bay by mechanical and chemical treatments is reopening intertidal lands to shorebirds and waterfowl (Patten and O'Casey 2007) as well as to fishing and recreation (Murphy 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported a reduction of light under the canopy of S. foliosa and S. virginica marshes relative to unvegetated mudflats, resulting in a lower abundance of microalgae and a subsequent decline in surface deposit feeders, while subsurface feeding groups such as tubificid oligochaetes and capitellid polychaetes were less affected (Lana and Guiss 1992;Levin et al 2006;Neira et al 2007;Whitcraft and Levin 2007). In our study, we found no evidence that dominance of diatoms (here sampled from the upper 1 cm of sediment) was less in salt marsh than in unvegetated mudflats (Online Resources 1 and 2).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated facilitation of other species or communities by salt marshes (Bruno et al 2003), while others demonstrated inhibition (Van Wesenbeeck et al 2007) or found no effect. The balance between facilitation and inhibition of benthic invertebrates by salt marsh plants may be tipped by the aboveground and belowground structure of the plant, and may therefore vary with plant species and successional stage (Brusati and Grosholz 2006;Neira et al 2007;Wang et al 2010).…”
Section: Introductionmentioning
confidence: 99%